Stem Cell Therapy for Lower Extremity Diabetic Ulcers: Where Do We Stand? - Yang, Mei (Hindawi Publishing Corporation, 2013)
The impairment of wound healing in diabetic patients is an important clinical problem affecting millions of patients worldwide. Various clinical and basic science studies show that stem cell therapy, as a regenerative medical therapy, can be a good solution. In this paper, we begin with an introduction of the cellular mechanism of the diabetic ulcer. We will then discuss the advantages and limitations of various stem cell therapies that have been under extensive recent study.